Dalits in the Past and Present: Experiences of Chamars from Nepal Tarai (Patan Pragya, 2023)
This paper is about the caste system, status of one of the Dalit community (Chamar) and the change taking place in such community over the period of time. Caste system is the division of people based on occupational diversity which is unique feature of Hindu society.According Hindu varna system, society is hierarchically divided as Brahmin, Kshatriya, Vaishya and Sudra. In this hierarchy, Dalits were kept at the bottom with duty as labourers and service providers. Belonging to Shudra varna they were discriminated in the name of so called untouchable caste. The results of untouchability were manifested in various areas of social practice including work and wage. It made Dalits to at the margin of the society. Later on the provision of punishment if any case of untouchability was found in practice was made. Even after the implementation of legal provision that considers discriminatory or untouchable practices against Dalits as illegal activities there is still the practice of untouchability. Till the date most of Dalits including Chamars in Tarai are engaged in age-old traditional occupation or manual works. Based on the previous literatures and few narratives collected through interviews this paper argues that the status of Chamar, one of the Dalit communities of Tarai was facing various problems including untouchability in the past and even today they are experiencing problems of various kinds including untouchability. However, social and cultural movement of Dalits in eastern Tarai of Nepal is a struggle for changing status of Dalits including Chamars.